2022
DOI: 10.1177/10755470221111558
|View full text |Cite
|
Sign up to set email alerts
|

Cutting the Bunk: Comparing the Solo and Aggregate Effects of Prebunking and Debunking Covid-19 Vaccine Misinformation

Abstract: An online experiment among a nationally representative YouGov sample of unvaccinated U.S. adults ( N = 540) leverages inoculation theory as a preliminary step in uniting the prebunking and debunking literature. By testing how prior attitudes toward Covid-19 vaccines interact with varying message interventions, the study finds that specific inoculation messages protect against misinformation, but only among those with preexisting healthy attitudes. Generic inoculation messages have wider application, offering b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…This is consistent with other research engaging underrepresented populations (Lee et al, 2023). While this inoculation-based strategy has been shown effective across audiences with differing preexisting attitudes on a topic (Amazeen et al, 2022), this study suggests that it merits future empirical analysis among populations vulnerable or receptive to science-related misinformation. An important challenge to information literacy interventions such as this, however, is evidence that they may have the unintended effect of prompting people to discount the accuracy of all types of information rather than only that which is false (Guay et al, 2022).…”
Section: Practical Implicationssupporting
confidence: 88%
“…This is consistent with other research engaging underrepresented populations (Lee et al, 2023). While this inoculation-based strategy has been shown effective across audiences with differing preexisting attitudes on a topic (Amazeen et al, 2022), this study suggests that it merits future empirical analysis among populations vulnerable or receptive to science-related misinformation. An important challenge to information literacy interventions such as this, however, is evidence that they may have the unintended effect of prompting people to discount the accuracy of all types of information rather than only that which is false (Guay et al, 2022).…”
Section: Practical Implicationssupporting
confidence: 88%
“…To supplement our primary analyses, we assessed a series of models that explicitly consider the heterogeneity within our samples. First, because the effectiveness of interventions designed to counteract COVID-19 misinformation may partly depend on respondents' initial beliefs ( Amazeen et al, 2022 ), we evaluated a set of models that interact each of the treatment conditions with the Wave 1 measure of the corresponding dependent variable. In no model did the interaction term reach statistical significance ( Figures A1.12-A1.15 ), implying that the effectiveness of this intervention does not significantly depend on respondents' prior levels of beliefs about COVID-19 vaccine risks.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent meta-analysis concluded that corrections exerted a positive but statistically insignificant influence on respondents' beliefs in COVID-19 vaccine misinformation ( Janmohamed et al, 2021 ). Other studies highlight the complexity of these relationships by demonstrating the moderating influence of respondents’ pre-existing attitudes ( Amazeen et al, 2022 ) or religiosity ( Schmid and Betsch, 2022 ) on the effectiveness of pre-bunking and debunking strategies. These results demonstrate the need to clarify the conditions under which corrective interventions succeed and to identify which strategies are most effective at countering inaccurate beliefs about COVID-19 vaccines among publics that have been widely exposed to anti-vaccine misinformation.…”
Section: Misinformation Correction and Covid-19 Vaccine Hesitancymentioning
confidence: 99%
See 1 more Smart Citation
“…We also performed a bidirectional analysis to detect the possible reverse causal relationship between CNS-regulated hormones and COVID-19. Anti-Coronavirus vaccines such as the BioNTech/Pfizer, Moderna, and Oxford/AstraZeneca vaccines have been proven to have prophylactic and therapeutic effects, which were highly recommended for protection [ 19 , 20 , 21 ]. However, more therapeutics for COVID-19 are still needed.…”
Section: Introductionmentioning
confidence: 99%